Dispersion behavior of 3D-printed columns with homogeneous microstructures comprising differing element shapes. (8th June 2017) - Nawada, Suhas; Dimartino, Simone; Fee, Conan
Highlights: Columns containing ordered lattices of particles were 3D printed. Several particle shapes and arrangements' plate heights were measured. Geometrical analysis of the printed parts show good replication of CAD models. Tetrahedral elements achieved the lowest plate heights in a simple cubic grid. Face-centered cubic was found to be the optimum arrangement of spheres. Abstract: We used additive manufacturing (3D printing) to create ordered porous beds from a range of geometric shapes, including truncated icosahedra (approximating spheres), tetrahedral, octahedral, triangular bipyramid, and stellar octangular particles. We show that the printed porous media were highly reproducible and had excellent fidelity in physically reproducing computer-aided design models, with differences between designed and experimentally measured particle locations within ±0.5%, and within 1.3% in terms of bed porosity. Experimental residence time distributions were measured and the reduced plate height, h, was determined under different reduced velocities (Peclet number, Pe = 4–400). The results (using equivalent particle diameter to non-dimensionalize) show that, for the simple cubic (SC) arrangement, tetrahedral particles had a lower plate height ( hmin = 1.56) than all other particle shapes tested, including spherical particles. We also, for the first time, experimentally validated computational predictions of the performance of SC, body centered cubic (BCC) and face centered cubic (FCC) arrangements of spheres, confirming that FCC is indeed superior ( hmin = 1.12) to SC ( hmin = 1.62). We conclude that the capability offered by additive manufacturing in controlling not only packing configuration but also shape, position and orientation of the geometric elements within the porous bed may, in the future, play a fundamental role in the design of highly efficient 3D-printed columns.